2022
DOI: 10.12973/eu-jer.11.2.1183
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Teachers’ Development in Using Technological Tools to Engage Students in Online Learning

Abstract: <p style="text-align: justify;">Technological tools are means by which online teaching could encourage the engagement of students, especially elementary students. The present research studies how elementary teachers develop their use of technological tools in their asynchronous and synchronous online teaching, specifically when this online teaching occurs during emergency education. The research was conducted in the academic year 2019/2020. We interviewed two elementary teachers, where one of them taught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Videos were used to satisfy the goal of providing learning materials. This shows that videos could serve a primary role in learning [41], particularly during emergency education [42]. Other studies reported presentations that were utilized in distance education due to times of emergency [43].…”
Section: Discussionmentioning
confidence: 82%
“…Videos were used to satisfy the goal of providing learning materials. This shows that videos could serve a primary role in learning [41], particularly during emergency education [42]. Other studies reported presentations that were utilized in distance education due to times of emergency [43].…”
Section: Discussionmentioning
confidence: 82%
“…The investigation conducted by Daher et al (2022b) examined the task design practices of math and science teachers engaged in online learning during the COVID-19 emergency education. 14 teachers participated in the study, with interviews serving as the primary data collection method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This shows that learning using flipped classrooms has been able to motivate students to learn. The technology used by the teacher in learning is in accordance with the type of interaction that the teacher makes with the students (Daher et al, 2022). Flipped classroom combined with computer technology effectively improves the quality of education and teaching (Li et al, 2018) and can advance knowledge about the integration of multimedia into learning.…”
Section: The Effectiveness Of Flipped Classroom In Learning To Write ...mentioning
confidence: 99%